Identification of a dual TAOK1 and MAP4K5 inhibitor using a structure-based virtual screening approach. (1st January 2021) - Chao, Min-Wu; Lin, Tony Eight; HuangFu, Wei-Chun; Chang, Chao-Di; Tu, Huang-Ju; Chen, Liang-Chieh; Yen, Shih-Chung; Sung, Tzu-Ying; Huang, Wei-Jan; Yang, Chia-Ron; Pan, Shiow-Lin; Hsu, Kai-Cheng
Abstract: The STE20 kinase family is a complex signalling cascade that regulates cytoskeletal organisation and modulates the stress response. This signalling cascade includes various kinase mediators, such as TAOK1 and MAP4K5. The dysregulation of the STE20 kinase pathway is linked with cancer malignancy. A small-molecule inhibitor targeting the STE20 kinase pathway has therapeutic potential. In this study, a structure-based virtual screening (SBVS) approach was used to identify potential dual TAOK1 and MAP4K5 inhibitors. Enzymatic assays confirmed three potential dual inhibitors (>50% inhibition) from our virtual screening, and analysis of the TAOK1 and MAP4K5 binding sites indicated common interactions for dual inhibition. Compound 1 revealed potent inhibition of colorectal and lung cancer cell lines. Furthermore, compound 1 arrested cancer cells in the G0/G1 phase, which suggests the induction of apoptosis. Altogether, we show that the STE20 signalling mediators TAOK1 and MAP4K5 are promising targets for drug research.